The Perceived Importance of Selected Information Characteristics for Strategic Capital Budgeting Decisions. - Larcker, David F. (The Accounting Review, 1981)
ABSTRACT: This study examines whether executives have similar preferences regarding information which may be used in making strategic capital budgeting decisions. Measures of perceived importance for selected information characteristics were obtained from 53 senior-level executives involved in strategic capital budgeting decisions. The results suggest that (1) executives have similar informational preferences, (2) the preferred information characteristics depend upon which stage of the decision-problem identification, alternative development, or selection–is being considered by the executive, and (3) environmental and organizational structure variables are not associated with an executive's informational preferences. The potential implications of these results for management accounting system design and for future research are discussed.